A case report of monkeypox as a result of conflict in the context of a measles campaign - E.L. Jarman; M. Alain; N. Conroy; L.A. Omam (Elsevier, 2022)
Introduction: Northwest and Southwest Cameroon suffer with ongoing conflict, associated with internal displacement of communities into bushland, violence and destruction of the health system. Case presentation: During a measles immunisation and surveillance campaign, following a measles outbreak, a 14-year-old boy was identified as having fever and a rash. This developed following close contact with a giant forest rat. He was diagnosed with monkeypox and this was confirmed by PCR. He was treated with oral cloxacillin and topical tetracycline for superadded bacterial skin and eye infections, and isolation policies were put in place. His rash improved over 7 days, when it scabbed over and his fever settled. Discussion: Recent displacement into a bush settlement away from agricultural opportunities increased his family's reliance on bush meat. Displacement away from established surveillance systems increased the risk of undetected transmission. This is the second confirmed case of Monkeypox in Cameroon in the last year, and the first in the Southwest region. Conclusion: Conflict led to the breakdown of surveillance systems, a lack of health personnel, destruction of health facilities and displacement of communities, which raised the risk of monkeypox outbreaks within Northwest and Southwest Cameroon. Surveillance for monkeypox is challenging due to clinical similarity to chickenpox. There is a risk of emergence in new regions with suitable hosts. The factors underlying the establishment of monkeypox infections in new regions are multifactorial and require a strong public health response for prevention and control. A OneHealth approach to emerging infectious diseases is essential.